Contribution of lower body segment rotations in various height soccer volley kicking - Sugi, S.; Nunome, H.; Tamura, Y.; Iga, T.; Lake, M. (Sports Biomechanics, 2022)
We aimed to quantify the contribution of lower body segment rotations in producing foot velocity during the soccer volley kick. Fifteen male experienced university players kicked a soccer ball placed at four height conditions (0, 25, 50 and 75 cm). Their kicking motion was captured at 500 Hz. The effectiveness of lower body segment rotations in producing forward (Ffv) and upward (Fuv) foot velocity were computed and time integrated. Major contributors for Ffv were a) left hip linear velocity, b) knee extension and c) pelvis retroflexion (the pitch rotation). The contribution of a) become smaller as the ball height increased while those of b) and c) did not change significantly. Moreover, the pelvis clockwise rotation (the yaw rotation) showed apparent contribution only for volley kicking (except 0 cm height). Major contributors for Fuv were 1) knee flexion, 2) hip internal rotation, 3) pelvis clockwise rotation (the roll rotation) and 4) hip flexion. The contributions of 1) and 4) become consistently smaller as the ball height increased, while those of 2) and 3) become larger systematically. Soccer volley kicking was found to have unique adaptations of segmental contributions to achieve higher foot position while maintain foot forward velocity.